Naturwissenschaftliche Untersuchungen zum Elfenbein von Sidi Harraz / Cap Sim und Mogador (Essaouira, Marokko) - Banerjee, Arun; Eiwanger, Josef; El Khayari, Abdelaziz; Enzmann, Frieder; Goebbels, Jürgen; Grootes, Pieter; Hüls, Matthias; Huth, Joachim; Marzoli, Dirce; Meinel, Dietmar; Michel, Jürgen; Nadeau, Marie-Josée (Madrider Mitteilungen, 2020)
Folgt.